Adolescents’ life satisfaction in Selangor, Malaysia: the effect of demographic differences - Chiong, Hoe Nee (Canadian Center of Science and Education, 2016)
This present study aims to describe the level of overall and domains-specific life satisfaction and to determine how differences in demographic variables can influence life satisfaction among adolescents in Selangor, Malaysia. The sample of the study consisted of 416 school-going adolescents, aged between 14 to 17 years old, who were selected through multi-stage cluster sampling from 12 secondary schools. The findings showed that adolescents generally reported positive level of life satisfaction. Differences in life satisfaction by age, gender and family structure were compared by t-test analysis. Younger adolescents display higher life satisfaction compared to older adolescents. Males reported higher level of life satisfaction in school domain and lower score in living environment domain compared to females. Respondents who were living in intact family arrangement also reported to have higher life satisfaction than those who were living with other types of family arrangements. In conclusion, cognitive judgment of adolescents’ life satisfaction differ with respect to their biological age, gender, and family structure.